Impact of Tourism on Quality of Life: A Case of Shimla, Himachal Pradesh - Asati, Shrey; Mandal, Nikhil; Mohapatra, Sameeksha (Calibrating Urban Livability in the Global South, 2024)
The study examines the urban challenges faced by Shimla, a historic hill station in India, facing rapid population growth and tourism influx. Consequently, the city faces issues such as water scarcity and non-compliance with construction norms, despite which it was ranked as the most livable city among smaller urban centres in India in the 2020 Ease of Living Index. The study provides insights into the sustainability and resilience of Shimla's urban environment amidst evolving demographic and environmental pressures. The study attempts to investigate the impact of tourism on the Quality of Life (QoL) of residents in Shimla Municipal Corporation over the past two decades. A multidimensional approach is used combining indicators from three indices via expert interviews and a pilot survey. The data for the selected indicators was collected and analyzed through a mixed-method approach through household surveys and secondary data sources. Through a Difference-in-Impact analysis, it is discerned that residents near tourist spots experience a higher deterioration rate in QoL compared to those residing farther away. Issues affecting QoL include infrastructural issues such as lack of parking spaces, and traffic congestion, environmental issues such as soil erosion, landslides, air, water, light and noise pollution and social issues such as youth drug addiction. The study tries to understand how tourism impacts the resident’s QoL both positively and negatively. The study's findings have policy implications and are instrumental in plan formulation and informed decision-making to balance the relationship between the tourism sector and the Quality of life of Shimla city residents.